Slam dunk - Stoudemire, Amar'e; Jessell, Tim (New York : Scholastic Inc., 2013)
When some of the older kids get on Amar'e for not being able to dunk, he sets a goal to make that happen soon. But when Amar'e's playing time is put on hold, he'll have to come to terms with all of the other things he's been neglecting
"Appeals to 3rd -5th graders, reading level: Grade 5"--P. [4] of cover
Keywords: Stoudemire, Amar'e -- Juvenile fiction; Basketball players -- Juvenile fiction; Friendship -- Juvenile fiction; Basketball stories; Basketball -- Fiction; Basketball stories